(untitled) (Estudios Gerenciales, 2012)
Recognizing that higher education institutions (HEI) are currently competing aggressively through competitive advantages and high service quality, the assessment of the service quality is essential to provide information on the effectiveness of educational plans and improvement programs. This article presents a study which tests the 5Q’s model proposed by Zineldin (2007), and examines the service quality factors that most impact on student satisfaction. Factor analysis and regression analysis showed significant variables in explaining student satisfaction as: trust developed toward the university and the academic program, and the perception they have of assessment techniques as a challenge to improve intellectual growth